2017
DOI: 10.1016/j.nano.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan enhances nanoparticle delivery from the reproductive tract to target draining lymphoid organs

Abstract: To prime adaptive immune responses from the female reproductive tract (FRT), particulate antigens must be transported to draining lymph nodes (dLNs) since there are no local organized lymphoid structures equivalent to those found in the respiratory or gastrointestinal tracts. However, little is known about how to safely and effectively navigate successive barriers to transport such as crossing the epithelium and gaining access to migratory cells and lymphatic drainage that provide entry into dLNs. Here, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…It was approved by the United States Food and Drug Administration (FDA) as it is biodegradable and biocompatible, with no side effects. Among the natural polymers, CS is frequently used in the design of nanomedicines [ 18 , 19 , 23 , 24 , 25 , 26 ]. Its cationic character and its solubility in water, as well as its biocompatibility and low toxicity, are attractive characteristics for using CS in the preparation of nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…It was approved by the United States Food and Drug Administration (FDA) as it is biodegradable and biocompatible, with no side effects. Among the natural polymers, CS is frequently used in the design of nanomedicines [ 18 , 19 , 23 , 24 , 25 , 26 ]. Its cationic character and its solubility in water, as well as its biocompatibility and low toxicity, are attractive characteristics for using CS in the preparation of nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Park et al . [ 114 ] reported that pre-treatment with chitosan can improve the movement of nanoparticles across the vaginal epithelium to LNs.
Fig.
…”
Section: Application Of Nanomedicines In Treating Cold Tumorsmentioning
confidence: 99%
“…Altering the core drug loading and the ratio of core to shell thickness of the coaxial spun fibers resulted in drug release that could range from several hours to several days . The potential for systemic release from local delivery of vaginal microbicides has been demonstrated by administering chitosan to improve local association with specific immune cells and transcytosis of carboxylate‐modified polystyrene NPs through the vaginal epithelium into the female reproductive tract draining lymph nodes, thereby improving both local function of the microbicide and adapting the vaginally administered NPs for systemic function . While the scalability of ARV loaded electrospun fibers has been demonstrated on production‐scale instruments, few in vivo studies have been performed for fiber biocompatibility and there is the potential for residual polymer remnants to remain following use .…”
Section: Nanostructured Systems For the Treatment Of Hivmentioning
confidence: 99%
“…118,136 By combining rapid release hydrophilic core polymers with sustained release hydrophobic shell polymers in coaxial electrospun fibers, precise control of the rate of release of maraviroc from the fibers prevents the burst release commonly observed in uniaxial electrospun fibers. 137 Altering the core drug loading and the ratio of core 138 While the scalability of ARV loaded electrospun fibers has been demonstrated on productionscale instruments, few in vivo studies have been performed for fiber biocompatibility and there is the potential for residual polymer remnants to remain following use. 118,139 Furthermore, both dendrimer and electrospun fiber biocompatibility are dependent upon polymer biocompatibility and degradation product toxicity.…”
Section: Electrospun Fibersmentioning
confidence: 99%